1991
DOI: 10.1002/bjs.1800780820
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and surgery for locally advanced cancer of the cardia and fundus: Phase II study with methotrexate and 5-fluorouracil

Abstract: Locally advanced cancer of the cardia and fundus might be cured by surgical resection. Poor results after surgery in stage IIIB and stage IV disease prompted a study of neoadjuvant chemotherapy. Treatment included four cycles of high doses of methotrexate (1.5 g/m2) and high doses of 5-fluorouracil (1.5 g/m2) followed by surgery in those patients with lesions then found to be resectable. Twenty patients with tumours staged as IIIB or IV were entered; 17 patients completed the four courses of chemotherapy and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1
5

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 14 publications
1
36
1
5
Order By: Relevance
“…A number of trials have tested neoadjux ant chemotherapy. demonstrating that preoperative chemotherapy is feasible and can increase the resection rate (Wilke et al 1990: Plukker et al 1991. Ajani et al 1993: RouDtier et al 1994: Kelsen et al 1996: Melcher et al 1996.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of trials have tested neoadjux ant chemotherapy. demonstrating that preoperative chemotherapy is feasible and can increase the resection rate (Wilke et al 1990: Plukker et al 1991. Ajani et al 1993: RouDtier et al 1994: Kelsen et al 1996: Melcher et al 1996.…”
mentioning
confidence: 99%
“…assessed preoperative chemotherapy in patients w ith unresectable gastric cancer at initial surgerx. This approach allow-ed radical surgery in about 40%' of patients with tumours previously unresectable (Wilke et al 1990: Plukker et al 1991.…”
mentioning
confidence: 99%
“…Nevertheless, data from a small randomised trial that compared the use of FAMTX as preoperative therapy before surgery vs surgery alone in operable gastric cancer could not demonstrate that the FAMTX regimen was suitable as neoadjuvant chemotherapy, and the authors concluded that more active regimens should be tested in further randomised studies (Songun et al, 1999). It should be noticed that in preoperatively unresectable patients, a combination chemotherapy containing methotrexate and 5-FU was reported by Plukker et al (1991) to allow 40% of curative resections. In a further trial, 34 patients with unresectable gastric cancer were treated with either of the two neoadjuvant chemotherapies: FEMTXP (5-FU, epirubicin, methotrexate, cisplatin) or THP-FLPM (pirarubicin, 5-FU, leucovorin, cisplatin, mitomycin C).…”
Section: Discussionmentioning
confidence: 99%
“…6,8,10,[17][18][19][20] Despite these promising results, the OS could not be improved in comparison to results from studies administering conventional CT in metastatic gastric cancer. [2][3][4] The reasons for this could be as follows: (1) the present study selected far advanced disease as reflected by a rate of 65% patients with ECOG status 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple phase II studies have shown an increased rate of R0 resections and a median survival of 16-43 months. [5][6][7][8][9][10][11] Ongoing randomized trials are attempting to confirm these promising results from phase II studies. In the present study, we enrolled patients with metastatic or locally far-advanced irresectable tumors on a multimodality treatment approach including dose-intensive chemotherapy and surgery.…”
Section: Ment; Neoadjuvant Chemotherapymentioning
confidence: 99%